2015
DOI: 10.3399/bjgp15x684025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the economic crisis and social support on health-related quality of life: first wave of a longitudinal study in Spain

Abstract: BackgroundEconomic recession affects quality of life by increasing rates of mental disorders in particular. Social support can be an important protective factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 31 publications
1
18
1
1
Order By: Relevance
“…Three of the five papers examining non-communicable diseases focused on the incidence of cardiovascular disorders. A spike in emergency room visits with cardiac problems was seen in a week at the peak of economic meltdown in 2008 in Iceland (RR 1.26, 95% CI 1.07–1.49) 96 and an increase in the prevalence of hypertension in males between 2007 and 2009 97 was noted in Iceland. In Greece, incident acute myocardial infarction was higher during the crisis (RR 1.40, 95% CI 1.29–1.51).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the five papers examining non-communicable diseases focused on the incidence of cardiovascular disorders. A spike in emergency room visits with cardiac problems was seen in a week at the peak of economic meltdown in 2008 in Iceland (RR 1.26, 95% CI 1.07–1.49) 96 and an increase in the prevalence of hypertension in males between 2007 and 2009 97 was noted in Iceland. In Greece, incident acute myocardial infarction was higher during the crisis (RR 1.40, 95% CI 1.29–1.51).…”
Section: Resultsmentioning
confidence: 99%
“…94 A study using Google Trends found a significant increase in certain health queries during the recession, amounting to more than 200 million excess searches, including stomach ulcer and headache symptoms, hernia, chest pain, and arrhythmia. 95…”
Section: Self-reported Healthmentioning
confidence: 99%
“…These practices are consistent with the literature on social support to improve outcomes in a variety of crisis situations. [3][4][5][6][7][8] Well-functioning, close relationships support functions of coping successfully with adversity, and participating in opportunities for growth and fulfillment in the absence of adversity. These support functions are rooted in attachment theory, a theory that proposes that all individuals enter the world with propensities to seek proximity to close others in times of stress and to support the attachment and exploration behavior of close others.…”
Section: Addressing Core Values Of Postgraduate Programsmentioning
confidence: 99%
“…In Norway, poor social integration among elderly was related to higher mortality [ 15 ], and in the Netherlands poor emotional support was related to higher mortality [ 16 ]. In Spain a study found that among elderly a low social network was related to more hospital admissions [ 17 ] and that social support offered protection against the adverse effect of economic recessions on mental health [ 18 ]. However, most of these studies focused on single factors and single settings and therefore it is unclear what the relative impact of different aspects of support on health is.…”
Section: Introductionmentioning
confidence: 99%